(untitled) (Ameghiniana, 2013)
"A pterosaur remain from La Amarga Formation, Hauterivían-Barremian is comunicated. It is a right femur which resembles the Pterodactyloidea genera: Herbstosaurus, Callodactulus, Dsunganipterus and Pterodactylus. The Jurassic- Cretaceous pterosaurs from Argentina were recovered from different paleoenvironments: Herbstosaurus and remains from Río Belgrano Formation, marine; Pterodaustro and Puntanipterus, mediterranean; the described specimen from La Amarga, continental near the coast. The material was associated to camosaur teeth, sauropod remains remains from Río Belgrano Formation, marine; Pterodaustro and Puntanipterus, mediterranean; the describes specimen from La Amarga, continental near fue coast. The material was associated to camosaur teeth, sauropod remains and mammals remains. This assamblage, is the most varied of the continental Early Cretaceous of Argentina."